Consistency of the $k$-nearest neighbors rule for functional data - Younso, Ahmad (Comptes Rendus. Mathématique)
The problem of nonparametric classification by $k$-nearest neighbors rule in a general metric space will be considered. Consistency and strong consistency of the classifier will be established under mild conditions.